2014
DOI: 10.4103/2008-7802.157663
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and violence among Iranian adolescents and youth: A 10-year systematic review

Abstract: Background:Although the overwhelming majority of Iranian adolescents are well-adjusted, a substantial group exhibits high levels of maladjustment and deficient functioning. Escalation of criminal violence among the youth population has become a major public policy issue and a serious public health problem. In reviewing a 10-year literature, this article aimed to describe and propose primary assumptions regarding the correlates of aggressive and violent behaviors in Iranian adolescents and youth.Methods:Bibliog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Some studies have shown that financial hardship and poverty in childhood are associated with psychiatric problems 23–25. A systematic review showed that the prevalence of violence and aggressive behaviours is of concern among Iranian youth and adolescents; it is associated with sociodemographic characteristics and family environment 19. Another systematic review showed that a low SES was strongly associated with psychiatric problems and violent behaviours in adolescents, and the strength of these associations varied according to different SES indicators 19…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that financial hardship and poverty in childhood are associated with psychiatric problems 23–25. A systematic review showed that the prevalence of violence and aggressive behaviours is of concern among Iranian youth and adolescents; it is associated with sociodemographic characteristics and family environment 19. Another systematic review showed that a low SES was strongly associated with psychiatric problems and violent behaviours in adolescents, and the strength of these associations varied according to different SES indicators 19…”
Section: Introductionmentioning
confidence: 99%
“…Results of an international research on bullying and victimization have shown a wide range of difference around the world from 12% in Australia to 83% in Saudi Arabia [5, 6]. In a recent systematic review conducted in Iran, prevalence of bullying was 30% to 65% (7). Different studies have identified several factors associated with bullying such as gender, age, physical appearance, individual tendency, and family factors, including marital conflict, domestic violence, child abuse, and low income or unemployment (810).…”
mentioning
confidence: 99%
“…Nonetheless, in this large sample (N=3315 students), as many as 2% were injured in fights. Kelishadi & Heidari, 2014). And, in a sample of 1324 Jewish and Arab adolescents living in northern Israel, 56% of adolescents surveyed reported at least one form of physical violence, which may reflect the larger ongoing conflict in that country (Khoury-Kassabri et al, 2014).…”
Section: Verbal Versus Physical Violencementioning
confidence: 99%